Modelling and generating abstract images of Paul Klee style. (29th October 2019) - Zhao, Hanqing; Zhang, Kang
This paper presents our recent work on automatically generating Paul Klee style of abstract paintings. Based on Klee's Pedagogical Sketchbook and our own understanding and observation, we analyse Klee's paintings made in his final few years. The generation process is described in details and sample generated images styled on two of Paul Klee's paintings are also demonstrated. Having analysed the colour and composition of Klee's paintings, we can randomly adjust the parameters to present results with unique compositions and palettes. We also propose a workflow of generating abstract paintings. This framework helps developing a paradigm for abstract image generation process. Our approach is also highly scalable.